Evoking Malaysian architecture cultural identity through development of parametric bim - Ali, Maisarah; Jahn Kassim, Puteri Shireen; Mohd Nawawi, Norwina; Mohamad Suhaimi, Mohamad Saifulnizam; Dawood, Nashwan (2016)
The aim of this paper is to discuss and highlight the potentials of BIM objects platforms with particular references to parametric modelling in creating a design process which involve the systematic abstracting of constructional elements learned from traditional architecture into systems of ratios, rules, proportion and hierarchy for urban typologies and applications. The paper focused on the constructional language from the design vocabulary of Malay vernacular architecture which is essentially timber-based, and BIM tools are used to transmute elements of the vernacular into modern construction and typologies such as multistorey facades. 3D elements in a data base are mathematically studied through analysing the proportions of elements in elevation and programming such ratios and equation into the parametric modelling subprogram in BIM. With the aim of evoking identity in a dense city context, elements of the Malay vernacular can be reworked towards the transposition of identity in multistorey structures and applications to preserve the memory of cultural traditions in a dense city context. The capabilities of BIM is used to capture the essence of Malay identity into city-scale urban type from such as commercial and residential blocks through the capabilities of BIM. From an analysis of construction of Malay palace and villa architecture is studied in terms of proportions and mathematical rules and engaging both the parametric rules and a library of profiles and elements from the construction BIM database of Malay elements in architecture, a series of façade and formal templates can be generated and used as guidelines and elements to enhance the historical and visual character of a city.